Why Context Matters: Social Inclusion and Multilingualism in an Austrian School Setting - Jessner, Ulrike (Social Inclusion, 2017)
This article draws attention to language choice and language use of Austrian bi- and multilingual school children. We explore some implications of their linguistic practices with regard to social inclusion in an Austrian educational school setting. Pursuing a Dynamic Systems and Complexity Theory approach, we hypothesise that before language users actually use a language within a certain context, they have to evaluate the respective communicative situation by taking multiple contextual factors into consideration, meaning language users choose to use, or not to use, a language based on the socio-contextual information at hand. We consider these contextual factors to be most relevant as they provide the basis on which speakers can actually make use of a certain language within a given context. By drawing on examples of empirical data obtained through a language background survey, we examine some of the complex and dynamic interactions of contextual parameters influencing language choice and language use in the formal educational setting of classroom instruction. Based on the results of this study, we display a selection of the dynamic and complex interactions of pupils’ language use in one specific context as well as their language preferences and how these relate to social inclusion.